The benefits of introducing meeting points into flex-route transit services. (September 2019) - Zheng, Yue; Li, Wenquan; Qiu, Feng; Wei, Heng
Highlights: A meeting point strategy is proposed to improve the reliability of flex-route transit. A two-stage optimization problem is introduced into the design of flex-route transit operations. Mixed integer programming is employed to formulate the problem with a lexicographic objective function. Experiments indicate that the meeting point strategy could significantly reduce the rejection rate by up to 24%. Abstract: In this paper, to improve the reliability of flex-route transit service under uncertain travel demand, a meeting point strategy is proposed in which passengers can be picked up and dropped off either at their reserved stops or at meeting points that are within their acceptable walking distance. A two-stage optimization problem is introduced into the design of flex-route transit operations. Mixed integer programming (MIP) is employed to formulate the problem with a twofold objective: to serve as many requests as possible and to minimize the total trip time of the accepted passengers. A memetic algorithm is adopted to solve the problem in a reasonable amount of time. Simulation experiments based on a real-life flex-route transit service are conducted to assess the benefits of introducing meeting points. The results demonstrate that meeting points can significantly reduce the rejection rate by up to 24% at the cost of walking an acceptable distance. We also find that reducing the passenger fare to compensate for the inconvenience of walking to meeting points constitutes a win–win strategy that benefits both passengers and transit operators.